PREPARATION OF METALLIC CERIUM BY METALLOTHERMIC REDUCTION USING CERIUM OXIDE AS RAW MATERIAL - Nuryadi Saleh (Puslitbang tekMIRA, 2015)
Cerium is one of the rare earth elements (REE) which many are found in rare earth minerals of monazite. Cerium is widely used for metal alloys in stainless steel, permanent magnets and automotive industries. In Indonesia, researchs for cerium extraction from such minerals of monazite to procure metallic cerium have not been inten- sively carried out, although cerium is potentially promising as raw material for alloying. The present research aims to study the conditions of cerium oxide (CeO2) reduction process to yield metallic cerium (Ce). Cerium oxide reduction process was performed by a metallothermic method using a reductant of magnesium metallic powder and CaCl2 as a flux. The parameters studied during the experiments were the quantity of the reductant, the composition of the flux and temperature of the process. The best result of the experimental process obtains the yield of metallic cerium about 50%, while the metal purity is 91% Ce. The process took place under condi- tions of that the oxide sample and reductant ratio were 1 : 1, the flux addition was 1%, with temperature of the process at 1200°C for 3 hours.